Pensiero, percezione e linguaggio in W.V. Quine - Giancarlo Zanet (Rivista Italiana di Filosofia del Linguaggio)
Notwithstanding his well known behaviorism, Quine connects language learning to the ability of understanding others by means of empathy, namely perceiving what an other is perceiving. The paper discusses and resolves the prima facie oddity between this thesis and Quine's criticism of propositional attitudes. It analyzes the notion of empathy and the cognitive mechanism underlying it. It explains also the role of empathy and of mindreading abilities in language learning and understanding others. Comparing Quine's account of mindreading to the main options in the current debate on the topic, it assess the validity of the Quinean inspired blend of rationality-based and hybrid view-based strategies to explain mindreading